Evaluating the Effect of firm Characteristics on Capital Structure - Abulfazl Ghadiri Moghadam, Ph.D; Fateme Asadian (مجله توسعه و سرمایه, 2010)
Different financial decisions are necessary for financial prosperity and also firm continued activity. An incorrect decision about financial structure may lead into financial pressures and finally bankruptcy. Managers usually determine firms structure like that the firm value becomes highest. Obviously managers' decision makings about the ways of providing firm financial resources are considered as a given strategy to adjust decisions considering the expedients of economic environment and also regarded as an appropriate model for increased efficiency of thought dominating firm function. The purpose of this research is to evaluate the effect of firm characteristics (quick ratio, interest coverage ratio, income growth, firm size, debt ratio, Tehran stock exchange) on capital structure whether mentioned cases influence the financial structure of firm. Obtained results specify that there is a significant relationship between quick ratio and interest coverage ratio of firm with firm debt ratio (capital structure). The method which has been used in this research is deductive. This research is an applied one in which real information and statistical methods have been used for proving the hypotheses. Samples have been selected randomly during time period of 2002 through 2006 and SPSS software has been used for analyzing data.